Application of ICT to Enhance Writing Skill: A Qualitative Study - Janah, Rohmatul; Tusino; Dewi, Puspa (Proceeding International Conference on Education, 2025)
This study investigates the application of Information and Communication Technology (ICT) to enhance students’ writing skills in a vocational school setting. Conducted with 32 eleventh-grade students in the Computer Network Engineering program at SMK Pancasila 1 Kutoarjo, this qualitative descriptive research employed classroom observation, questionnaires, and semi-structured interviews to gather data. Findings reveal that ICT integration significantly improves students’ writing proficiency by fostering engagement, expanding vocabulary and grammar accuracy, and reducing writing anxiety through collaborative platforms. Students reported that ICT tools make writing more interesting, promote autonomy, and increase motivation. However, challenges such as limited internet connectivity, insufficient devices, and uneven digital literacy were also identified. Overall, the study concludes that ICT has great potential to support effective writing instruction in vocational schools, provided that infrastructural and pedagogical challenges are adequately addressed. Future research is recommended to explore hybrid ICT-based approaches and long-term impacts on academic writing performance.